IMPLEMENTATION OF DEEP DISCOVERY LEARNING METHOD IMPROVING STUDENT LEARNING OUTCOMES IN SUBJECTS FIQIH IN MADRASAH ALIYAH - Afifah, Wardah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Global changes and demands for scientific progress The background for this research, as a fiqh teacher should be we can create learning that produces quality Education. So teachers have to anticipate it in various ways various learning methods and models that can improve student exploration and contribution so as to improve results student learning using the discovery learning method. In this research we focus on two problem points: (1) how implementation of discovery learning learning methods in increase students' understanding of fiqh subjects in MA Nurul Jadid? (2) how will student learning outcomes improve after through discovery learning methods in subjects fiqh at MA Nurul Jadid. The aim of this research is to know the discovery learning method in fiqh subjects and to determine the development and effectiveness of the discovery method learning in fiqh subjects at MA Nurul Jadid. This research is a qualitative research. Approaches and types used is descriptive research. Descriptive research is a form of research intended to describe or describe phenomena well with make a description of the problems identified. Technique Data collection here is through interviews structured, observation, passive participants and documentation. Analysis data by collecting data, data reduction process, presentation data as well as withdrawal/verification or what is called a conclusion. The data checking technique uses degree criteria trust, transferability, luck and certainty. The results of research conducted by researchers include: The implementation of discovery learning begins with providing a stimulus and questions about the material on ijtihad and madzhab in the book In the second class XII fiqh lesson, student learning outcomes were higher than before using the discovery learning method.